APPRENTICESHIP PROGRAM FOR PROSPECTIVE PROFESSIONAL INDONESIAN ARCHITECTS - Riskiyanto, Resza (architecture department, Engineering faculty, Universitas Diponegoro, 2023)
This report was created to provide a detailed understanding of the architectural internship program required by the Indonesian Association of Architects as the only architect association recognized by law. This program must be taken by prospective architects before submitting an architect registration certificate to be recognized as a professional architect. The purpose of submitting this report is also to correct the misunderstanding of the principles of a professional apprenticeship program which is generally equated with an interbship program conducted while studying architecture. This report explicitly shows that apprenticeship programs that are recognized as part of the process for submitting professional architects are apprenticeship programs for a minimum of two years which are followed after completing architectural education.